Occupational Stress and Mental Health: A Comparison Between Frontline Medical Staff and Non-frontline Medical Staff During the 2019 Novel Coronavirus Disease Outbreak - Zhang, Xie; Zhao, Ke; Zhang, Guohua; Feng, Ruihua; Chen, Jianjun; Xu, Dongwu; Liu, Xiaodong; Ngoubene-Atioky, Arlette J.; Huang, Hong; Liu, Yanlong; Chen, Li; Wang, Wei (Frontiers in Psychiatry, 2020)
Background: During an epidemic, both frontline and non-frontline medical staff endure stressful work circumstances that render their mental health a major public health concern. This study aims at investigating and comparing the prevalence and severity of mental health symptoms (i.e., anxiety, depression and insomnia) between frontline medical staff and non-frontline medical staff during the coronavirus disease 2019 (CIVOD-19) outbreak. It also seeks to evaluate the association of their mental health with occupational stress. Methods: A cross-sectional study was conducted in Wenzhou, China in February 2020. A total of 542 medical staff responded to the Generalized Anxiety Disorder Scale, the Patient Health Questionnaire, the Insomnia Severity Index, the Occupational stress Questionnaire, and a demographic data form. A stepwise linear regression was utilized to analyze the data. Results: Of the 524 participants, 31.3% reported depression, 41.2% reported anxiety, and 39.3% reported insomnia. Compared with the residents during the COVID-19 epidemic, medical staff experienced higher level of anxiety, depression and insomnia, especially the frontline medical staff. Furthermore, male, married medical staff with poorer physical health reported lower mental health. Frontline medical staff endorsed higher self-reported occupational stress, especially higher occupational hazards, than non-frontline medical staff. In addition, four indicators on occupational stress correlated positively with mental health symptoms. Regression analyses found a significant association between occupational stress and mental health symptoms in both frontline and non-frontline medical staff during COVID-19 outbreak. Conclusion: The results indicated that medical staff had more occupational stress, and frontline medical staff experience higher levels of anxiety, depression and insomnia than non-frontline medical staff and residents during the COVID-19 epidemic. These findings emphasize the importance of occupational stress management interventions to improve the mental health of the medical staff during a biological disaster